Shift in SARS-CoV-2 variants of concern from Delta to Omicron was associated with reduced hospitalizations, increased risk of breakthrough infections but lesser disease severity - Fridah Mwendwa; Akbar Kanji; Ali Raza Bukhari; Unab Khan; Ayesha Sadiqa; Zain Mushtaq; Nosheen Nasir; Syed Faisal Mahmood; Uzma Bashir Aamir; Zahra Hasan (Elsevier, 2024)
Background: COVID-19 epidemiology changed with the emergence of SARS-CoV-2 variants of concern (VOC). Pakistan administered mostly inactivated vaccines. We investigated the association between VOC and breakthrough infections in a mixed-vaccination-status population of Karachi. Methods: We investigated SARS-CoV-2 VOC tested in 392 respiratory specimens collected between May and December 2021. Data for age, sex, hospital admission, vaccinations, together with CT values of the diagnostic PCR test were analyzed. Results: The median age of COVID-19 cases tested was 40 (27−57) years and 43.4% were female. Delta variants were most common (56.4%) followed by Alpha (15.9%), Omicron (12.2%), Beta/Gamma (11.3%), and others (4.3%). Eighteen percent of cases were hospitalized whereby, predominant VOC were Beta/Gamma (40.8%), Alpha (35.2%) and Delta (22.5%). Overall, 55.4% of individuals were fully vaccinated, 7.4% were partially vaccinated and 37.2% were unvaccinated. Most (74.6%) inpatients were unvaccinated. Vaccines comprised inactivated (85.34%), single-shot vector (8.62%), two-shot vector (3.02%) and mRNA (3.02%) types. Omicron variants showed lower viral loads as compared to Alpha, Beta/Gamma, and Delta (p = 0.017). The risk of infection with Delta and Omicron variants was higher, 8 weeks after vaccination. The majority of those with breakthrough infections after receiving inactivated vaccines acquired COVID-19 within 4 months of vaccination. Conclusion: Our data highlights the shifting of VOC from Delta to Omicron during 2021 and that COVID-19 vaccinations reduced both hospitalizations and viral transmission. It informs on the increased risk of breakthrough infection within 8 weeks of vaccination, indicating the need for booster vaccinations.